Defining Early-Onset Colon and Rectal Cancers - Jacobs, Daniel; Zhu, Rebecca; Luo, Jiajun; Grisotti, Gabriella; Heller, Danielle R.; Kurbatov, Vadim; Johnson, Caroline H.; Zhang, Yawei; Khan, Sajid A. (Frontiers in Oncology, 2018)
Background: Colorectal cancer (CRC) incidence is rising in the young, yet the age of those affected is not clearly defined. In this study, we identify such cohorts and define clinicopathological features of early-onset colon and rectal cancers. Methods: The Surveillance, Epidemiology and End Results Program (SEER) database was queried to compare clinicopathological characteristics of colon and rectal cancers diagnosed during 1973-1995 with those diagnosed during 1995-2014. Results: We identified 430,886 patients with colon and rectal cancers. From 1973-1995 to 1995-2014, colon cancer incidence increased in patients aged 20 to 44 years, while rectal cancer incidence increased in patients aged ≤54 years. The percent change of cancer incidence was greatest for rectal cancer with a 41.5% (95% confidence interval (CI): 37.4-45.8%) increase compared to a 9.8% (CI: 6.2-13.6%) increase in colon cancer. Colon cancer has increased in tumors located in ascending, sigmoid, and rectosigmoid locations. Adenocarcinoma histology has increased in both colon and rectal cancers (P<0.01), but mucinous and signet ring cell subtypes have not increased (P=0.13 and 0.08, respectively). Incidence increases were race-specific, with rectal cancer seeing similar rises in white (38.4%, CI: 33.8-43.1%) and black populations (38.0%, CI: 26.2-51.2%), while colon cancer as a whole saw a rise in white (11.5%, CI: 7.2-15.9%) but not black populations (-6.8%, CI: -14.6-1.9%). Conclusions: Our study underscores the existence of key differences between early-onset colon (20-44 years) and rectal cancers (≤54 years) and provides evidence-based inclusion criteria for future investigations. We recommend that future research of CRC in the young should avoid investigating these cases as a single entity.